Grupos nos quais o conjunto dos comutadores possui cobertura finita por subgrupos cíclicos - Silva, Ana Shirley Monteiro da (2010)
Given a word w and a group G, suppose that the set can be Gw covered by finite cyclic subgroups. It is true that w(G) can also be covered by finite cyclic subgroups? This dissertation will show that the answer is positive for the word switch.